PERANCANGAN DAN IMPLEMENTASI APLIKASI SISTEM PENGENDALIAN MUTU UNTUK MENINGKATKAN EFEKTIFITAS OPERASIONAL PADA KANTOR JASA PENILAI PUBLIK (KJPP) - Muchammad Hamdani; Zeze Zakaria Hamzah; Muhlis Muhlis; Jarot Wuryanto; Jaka Permana (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
Each company has a need to have a system that can support its business processes, such as The Public Assessor Services (KJPP) that play an important role in determining the economic value of a property. The assessment process carried out by the company KJPP has arried out by hand at less efficient value. The creation of web-based applications for the quality control system is aimed at making it easier in the assessment process and meeting the current standard rules obligations. The prototype aims to design and implement applications for the quality control system of the company in order to make the assessment process more effective. The prototype generated applications for the quality control system on the KJPP using the System Enterprise Resource Planning (ERP) system using the double diamond method. In the double diamond, there are four major stages: discover, define develop, deliver. The results of the prototype to the evaluation point out that the application of this quality control system is very effective for improving the operation of the KJPP is shown by the evaluation using a col 4 point scale with a 3.8 value of satisfaction from 4 (94%).